The Role of Teachers and the Implementation of Islamic Character Education Methods in Madrasah Students - M. Syafrian Syaputra (Yayasan Bayt Shufiya Nusantara, 2025)
This study explores the role of teachers in implementing Islamic character education methods for students at MTs Amin Darussalam, Desa Bandar Setia, Kecamatan Percut Sei Tuan, Indonesia. Using a qualitative field research approach, data were collected through structured interviews with key informants, including teachers and the head of the madrasah. The findings reveal that teachers adopt three core strategies in shaping students’ character: exemplary conduct, moral advice, and behavioral habituation. These methods contribute significantly to the development of students' moral values, discipline, and social ethics in accordance with Islamic teachings. The study concludes that character formation in madrasah education requires active teacher involvement supported by institutional policies and a positive school culture. The implications emphasize the importance of strengthening teachers' competencies in Islamic character pedagogy and enhancing collaboration between school and family to ensure continuous moral development.